Theology disrupted: Doing theology with children in African contexts - Mahlangu, Elijah (HTS teologiese studies, 2016)
The thrust of this article is an attempt to respond to the question whether we can read and interpret the bible in Africa from the child theology vantage point. The author’s answer is in the affirmative in two ways: Firstly, it is that the majority of children in Africa are facing abuses of unprecedented proportions. Historically and traditionally, African scholars always read and interpreted the bible with African lenses. The African bible critic and exegete should be part of the church, the body of Christ which ought to be a lotus of healing. Theologising in the context of the crisis of the ‘child’ in Africa is fairly a new development and needs to be aggressively pursued. The second aspect of this author’s response is that when Christianity entered the Graeco-Roman as well the Jewish milieu, it used the family symbolism such as father, brothers, love, house of God, children of God, and so on. The New Testament authors therefore used family as reality and metaphor to proclaim the gospel. The African theologian, critic and exegete, is therefore in this article challenged to make a significant contribution using the African context in that, ‘… the African concept of child, family and community appears to be closer to ecclesiology than the Western concepts’.